The systemic capillary leak syndrome following COVID-19 vaccine - Chengjie Zhao; Ruirui Xue; Kaile Zhao; Ruoyan Lei; Mingyi Zhao; Lin Liu (Taylor & Francis Group, 2024)
The COVID-19 outbreak has been declared the sixth Public Health Emergency of International Concern certified by the World Health Organization. With the extensive application of COVID-19 vaccines, rare but serious adverse reactions have gradually emerged, among which systemic capillary leak syndrome (SCLS) deserves our attention. SCLS is difficult to diagnose. Not only can it exacerbate various diseases, but also can lead to pulmonary edema, kidney failure, and even death. We summarized and discussed case reports of SCLS induced by COVID-19 vaccines to raise awareness of COVID-19 vaccine-associated rare diseases. We conducted a comprehensive search in Web of Science, PubMed and Embase and collected case reports of SCLS induced by COVID-19 vaccine before February 19, 2024. We identified and analyzed 12 articles, encompassing 15 cases. We synthesized the data to summerize possible mechanisms of SCLS, clinical manifestations, differential diagnoses, and therapeutic approaches. Most SCLS occurred after vaccination with the Pfe-Biontech mRNA vaccine (9/15) and following the second vaccination (10/15). Almost all patients experienced hypotension (13/15) and tachycardia (11/15). Most patients received intravenous fluids (9/15) and corticosteroids (9/15). 11 patients were recovered and were discharged, while 4 patients died. Inflammation and endothelial cell damage may be linked to SCLS and COVID-19 vaccines. These findings highlight the necessity of focusing on serious adverse reactions of COVID-19 vaccines and the urgency to reconsider the safety of COVID-19 vaccines.